Kemukjizatan Al-Qur’an dalam Pengembangan Ekonomi Syariah: Analisis Terhadap Prinsi-Prinsip Bisnis Islam Dalam Al-Qur’an - Khaerunnisa, Syarifa (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This study explores the miraculous nature of the Qur'an in the context of developing Islamic economics by focusing on the analysis of Islamic business principles found in Surah Al-Baqarah. Although much has been discussed, this research aims to provide deeper insights into these principles through the perspective of Qur'anic exegesis. The objective is to present a more detailed study of the principles within the Qur'an, particularly in Surah Al-Baqarah, by applying exegetical approaches from linguistic and jurisprudential perspectives. This approach is expected to offer a more holistic and profound understanding of the messages contained in the Qur'anic text related to Islamic business principles.Through the method of tafsir analysis, this study aims to identify, analyze, and interpret the Islamic business principles found in Surah Al-Baqarah. The findings of this research are expected to make a significant contribution to the development of Islamic economic thought and the enhancement of Islamic business practices. It is hoped that the results of this study will provide clearer insights into the Islamic business principles contained in the Qur'an and offer academic recommendations that can serve as guidelines for practitioners, academics, and policymakers in strengthening Islamic economics in a more sustainable and equitable manner.Moreover, this study seeks to explore the relevance of these principles in the modern context and the current global economic challenges. Thus, this research not only aims to add to the scholarly literature but also to provide practical solutions that can be implemented in contemporary Islamic business practices, thereby enhancing the welfare of the community and strengthening the economic foundation based on Islamic values.